COMPARATIVE STUDY OF THIRD GRADE BLOOD FLOW THROUGH STENOSED ARTERY WITH CONSTANT AND VARIABLE VISCOSITIES - A, Jimoh, (IJRDO -JOURNAL OF MATHEMATICS, 2021)
Mathematical models for the comparative study of blood flow through stenosed artery with constant viscosity and variable viscosity dependent on red blood cells concentration (hematocrit) taking into consideration the externally applied magnetic field and slip velocity is presented. The laminar, incompressible, fully developed, non-Newtonian (third grade) flow of blood in an artery having stenosis is numerically studied. Effect of variable viscosity, slip velocity and magnetic field in the blood flow with constant and variable viscosities are discussed of analytically and graphically. All the flow characteristics are established to be effected due to the combined effects of the variable viscosity, magnetic field and slip velocity. Analytical expression for both blood flow models with constant and variable viscosities for the velocity profiles, volumetric flow rate, shear stress and resistance to flow are derived. The study provides an insight into the effects of variable viscosity, magnetic and slip velocity on the velocity profiles, volumetric flow rate, shear stress and resistance to flow on blood flow models with constant and variable viscosities